2022
DOI: 10.2147/clep.s381289
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Drugs Associated with Lower Risk of Parkinson’s Disease Using a Systematic Screening Approach in a Nationwide Nested Case–Control Study

Abstract: Introduction: Drugs for other indications may be repurposable as disease-modifying drugs for Parkinson's disease (PD). A systematic hypothesis-free approach can enable identification of candidates for repurposing. We applied a hypothesis-free systematic approach to identify drugs associated with lower risk of PD to discover candidates with potential for repurposing as disease-modifying drugs for PD and to illustrate challenges in observational studies that simultaneously investigate multiple repurposing candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…CYP2W1 is expressed in a cancer-specific way and converts pro-dugs as well as fatty acids like arachidonic acid ( Pan and Ong, 2017 ). CYP20A1 is highly expressed in the brain, especially in the Substantia nigra ( Stark et al, 2008 ; Lemaire et al, 2016 ) , and a connection to methotrexate toxicity has been found ( Papapetropoulos et al, 2004 ; Aslibekyan et al, 2014 ) although this finding is controversial ( Koponen et al, 2022 ). Interestingly, for CYPs of the CYP4 family (CYP4A22, CYP4X1 and CYP4Z1) a participation in fatty acid conversion and epoxide formation of eicosatrienoic acids has been described ( Zöllner et al, 2009 ; Carver et al, 2014 ; McDonald et al, 2017 ; Durairaj et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…CYP2W1 is expressed in a cancer-specific way and converts pro-dugs as well as fatty acids like arachidonic acid ( Pan and Ong, 2017 ). CYP20A1 is highly expressed in the brain, especially in the Substantia nigra ( Stark et al, 2008 ; Lemaire et al, 2016 ) , and a connection to methotrexate toxicity has been found ( Papapetropoulos et al, 2004 ; Aslibekyan et al, 2014 ) although this finding is controversial ( Koponen et al, 2022 ). Interestingly, for CYPs of the CYP4 family (CYP4A22, CYP4X1 and CYP4Z1) a participation in fatty acid conversion and epoxide formation of eicosatrienoic acids has been described ( Zöllner et al, 2009 ; Carver et al, 2014 ; McDonald et al, 2017 ; Durairaj et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The association with a reduced PD risk for drugs acting on RAS (C09) has previously been described among others in an early review of experimental data and clinical observations, 17 2 retrospective cohort studies of the risk for PD among 107,207 patients treated for hypertension 18 and among 62,228 patients with ischemic heart disease, 19 and 1 nationwide screening using a nested case-control study of 10,183 PD cases and 67,849 controls. 20 Furthermore, a clinical prospective study of 107 patients with PD found that treatment with ARB improved cognitive function. 21 The 3 epidemiologic studies found that the use of the ARBs was associated with a reduced PD risk, whereas no association was found for the ACEIs.…”
Section: Discussionmentioning
confidence: 99%
“…The drugs for obstructive airway diseases (R03, including β2-agonists) were shown to be related to reduced PD risk in newly published studies on French national health data 39 and Finnish health data. 20 Specifically, β2-agonists have been previously investigated for a role in PD. Mechanistically, selective β2AR activation suppresses the degeneration of nigral dopamine neurons, prevents loss of striatal dopamine, and rescues movements in multiple rodent models of PD.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found no evidence of confounding by indication for an inverse methotrexate-PD association in our population [ 37 ]. Another study found a stronger inverse methotrexate-PD association [ 30 ], but did not observe the association when restricting to rheumatoid arthritis patients [ 38 ]. Still, another study restricted to rheumatoid arthritis patients did find an inverse methotrexate-dementia association very similar to our association for AD [ 39 ].…”
Section: Discussionmentioning
confidence: 99%